The Relationship of Motivation for Entering the Faculty ff Medicine and Dentistry on Student's Academic Achievement - Mei Enjelika br Lubis, Rima; Lister, Clarissa; Hendriani Djuang, Michelle (Riviera Publishing, 2024)
Education is essential in modern society, both politically and economically. Medical training plays a critical role in producing qualified doctors. Competent doctors, the result of training provided by quality medical education institutions, provide quality health services to the community. Motivation is significant in determining learning success. This research aims to determine the relationship between motivation for entering medical and dental faculties and student's academic achievement. An online survey was used to collect data for this research. The sample population of the research was medical and dental students from Prima Indonesia University. The strength of the Motivation for Medical Students (SMMS) instrument, translated into Indonesian, was used to collect data for student motivation. 123 out of 493 medical and dental students participated in this research. Survey results show that suitability and interest are why students enter medical and dental faculties. The Spearman's rho correlation test shows no significant relationship between motivation variables and GPA, with Sig. (2-tailed) of 0.303 where p > 0.05. The Mann-Whitney test shows no statistically significant difference between the two genders with Sig. (2-tailed) of 0.558 where p > 0.05. This study shows that although there are various reasons and motivations for entering medical and dental faculties, there is no relationship between the above and academic achievement.